Substituted 2-[(2-Oxo-2H-[1,2,4]triazino[2,3-c]quinazolin-6-yl)thio]acetamides with Thiazole and Thiadiazole Fragments: Synthesis, Physicochemical Properties, Cytotoxicity, and Anticancer Activity - Kovalenko, S. I.; Nosulenko, I. S.; Berest, G. G.; Voskoboynik, A. Yu.; Antypenko, L. N.; Antipenko, A. N.; Katsev, A. M. (My University, 2012)
The series of novel N-R-2-[(3-R-2-oxo-2H-[1,2,4]triazino[2,3-c]quinazolin-6-yl)thio]acetamides with thiazole and thiadiazole fragments in a molecule were obtained by alkylation of potassium salts 1.1–1.4 by N-hetaryl-2-chloro-acetamides and by aminolysis of activated acids 2.1–2.4 with N,N'-carbonyl-diimidazole (CDI). The structures of compounds were determined by IR, 1H NMR, MS, and EI-MS analysis. The results of cytotoxicity evaluated by the bio-luminescence inhibition of bacterium Photobacterium leiognathi, Sh1 showed that the compounds have considerable cytotoxicity. The synthesized compounds were tested for anticancer activity in NCI against 60 cell lines. Among the highly active compounds 3.1, 3.2, and 6.5, 2-[(3-methyl-2-oxo-2H-[1,2,4]triazino[2,3-c]quinazolin-6-yl)thio]-N-(1,3-thiazol-2-yl)acetamide (3.1) was found to be the most active anticancer agent against the cell lines of colon cancer (GI50 at 0.41–0.69 μМ), melanoma (GI50 0.48–13.50 μM), and ovarian cancer (GI50 0.25–5.01 μM). The structure-activity relationship (SAR-analysis) was discussed.
Keywords: [1,2,4]Triazino[2,3-c]quinazolines; Thiazoles; Thiadiazoles; Anticancer; SAR; Bioluminescence inhibition